Influence of soluble salt matrix on mechanochemical synthesis of lanthanum cobaltate nanoparticles - Supachai Sompech (2018)
Mechanochemical reaction of lanthanum cobaltate (LaCoO3) nanoparticles was performed by milling mixtures of LaCl3-7H2O, CoCl2and Na2CO3, with no addition and addition of soluble salt matrix (NaCl). The purposes of this work were to synthesize LaCoO3nanoparticles via mechanochemical process and to study the effect of soluble salt matrix on the average particle size and specific surface area. The three-stage process consisting of mechanical milling, subsequent heating and washing with distilled water was used to synthesize of LaCoO3nanoparticles. The results indicated that the average particle size (D[4,3]) and the specific surface area are as a function of the soluble salt matrix concentration. Moreover, SEM images revealed that the addition of soluble salt matrix can improve the dispersion of LaCoO3, nanoparticles.